Characteristics of Marine Envenomation Cases in Kepulauan Seribu District Hospital, Indonesia - Hadiki Habib; Johan Salim; Yogie Dwi Nugroho; Fitran Amansyah; Donny Alpha Edison; Ghamal Ahmad Pramana; Ma’mun; Salinah (PT Kalbe Farma Tbk., 2018)
Backround Kepulauan Seribu district hospital frequently manage cases of marine envenomation. Recognizing characteristics of envenomation are needed to develop clinical guideline. Method. A cross sectional study during January to December 2016. Cases of marine envenomation in the Emergency Room of Kepulauan Seribu District Hospital were documented by structured medical records. Pictures of the affected body parts were also taken. Results. Sixteen cases of marine envenomation were documented. Most subjects (87,5%) were domestic tourists. The average age of the subjects were 21,12 years old. Pain is the most common chief complaint (81,3%). Most subjects seek medical treatment less than 2 hours after the incident (56,3%). Lionfish sting was the most common cause (50%) followed by jellyfish sting (25%), other causes were stingray, sea urchin, catfish, and sea snake. Diagnosis were mostly made by focused anamnesis for animal identification (62,5%) and examination of the wounds (25%). Puncture type wound was the most common pattern (68,75%). Initial management by hot water immersion were only done in 56,3% cases. Conclusion. Lionfish sting was the most common cause of the envenomation cases in Kepulauan Seribu region. Identification of the animals and the wound patterns were the most common diagnostic methods. Hot water immersion was found to be effective to relief the pain but its use in medical management was not extensively applied.